Trainee participation during screening colonoscopy does not affect ADR at subsequent surveillance, but may result in early follow-up - Eckardt, Alexander J.; Kheder, Joan; Basil, Anjali; Silverstein, Taryn; Patel, Krunal; Mahmoud, Mohamed; Al-Azzawi, Yasir; Ellis, Daniel; Gillespie, William; Carrasquillo Vega, Yoel; Person, Sharina D.; Levey, John M. (Endoscopy International Open, 2020)
Background and study aims Training future endoscopists is essential to meet rising demands for screening and surveillance colonoscopies. Studies have shown conflicting results regarding the influence of trainees on adenoma detection rates (ADR). It is unclear whether trainee participation during screening adversely affects ADR at subsequent surveillance and whether it alters surveillance recommendations.Patients and methods A retrospective analysis of average-risk screening colonoscopies and surveillance exams over a subsequent 10-year period was performed. The initial inclusion criteria were met by 5208 screening and 2285 surveillance exams. Patients with poor preparation were excluded. The final analysis included 7106 procedures, including 4922 screening colonoscopies and 2184 surveillance exams. Data were collected from pathology and endoscopy electronic databases. The primary outcome was the ADR with and without trainee participation. Surveillance recommendations were analyzed as a secondary outcome.Results Trainees participated in 1131 (23 %) screening and in 232 (11 %) surveillance exams. ADR did not significantly differ (P = 0.19) for screening exams with trainee participation (19.5 %) or those without (21.4 %). ADRs were higher at surveillance exams with (22.4 %) and without (27.5 %) trainee participation. ADR at surveillance was not adversely affected by trainee participation during the previous colonoscopy. Shorter surveillance intervals were given more frequently if trainees participated during the initial screening procedure (P = 0.0001).Conclusions ADR did not significantly differ in screening or surveillance colonoscopies with or without trainee participation. ADR at surveillance was not adversely affected by trainee participation during the previous screening exam. However, trainee participation may result in shorter surveillance recommendations.